Research progress on porous materials for capturing carbon dioxide from flue gas - Zemin ZHAO; Huimin GAO; Ting QU; Jieying JING; Wenying LI (Meitan xuebao, 2023)
The CO2 emission caused by fossil fuel combustion is one of the important reasons for global warming and extreme weather. At present, fossil fuel is still the primary energy in China and CO2 emission remains high. The use of low-cost and energy-efficient CO2 capture methods can effectively alleviate the occurrence of above situation. Compared with the alcohol amine solution absorption method, the adsorption method has the advantages of low energy consumption, less damage to the equipment and excellent cycle stability, etc. However, the adsorption materials usually involve a complex preparation process and the cost is high. Therefore, it is urgent to find a kind of new adsorption material with low cost and excellent CO2 adsorption performance to achieve an efficient CO2 capture. In this study, the properties of ideal porous adsorption materials are introduced, the influence of other gases such as water vapor and SO2 in the flue gas on the CO2 adsorption performance of porous materials, and the ways to improve the CO2 adsorption performance of porous materials are mainly discussed. Porous materials have the advantages of large specific surface area, and adjustable pore size, etc., among which the silicon-based mesoporous materials and activated carbon have low prices, and the MOFs materials have various functions. These characteristics make porous materials widely used in the field of CO2 capture. However, it is worth noting that the molecular sieves and silicon-based mesoporous materials are highly sensitive to water vapor. The MOFs materials are less affected by water vapor than the molecular sieves, but their adsorption capacity is relatively low under low pressure and their preparation cost is relatively high. Activated carbon materials also have disadvantages such as low adsorption capacity. Therefore, various porous materials need to be constantly modified to improve their adsorption performance, and most of the modification methods of porous materials focus on pore structure regulation and surface modification. Future research needs to further explore the internal mechanism of CO2 adsorption by porous materials and the synergistic regulation of surface modification and pore structure.